Plantas medicinais: contextualizando saberes dos educandos do IFAM campus Tefé, Amazonas - (:unkn) unknown (Universidade Federal do Amazonas, 2022)
As part of the great diversity of plant species in the Amazon Biome, medicinal plants are still widely used by local populations in the treatment of various diseases. These populations have a vast natural pharmacopoeia in their environment. Studies on these plants can provide innumerable information about the social groups that hold this knowledge and the different management and conservation strategies of these species. From this reflection, the idea arose of studying an interdisciplinary didactic approach to contextualize the teaching of environmental sciences from the knowledge of students and family members about medicinal plants. Thus, we proposed to develop didactic material for the learning of environmental sciences from the students' perception of medicinal plants. The study was developed at the IFAM Campus Tefé with students from the 3rd grade of the Technical Course in Administration integrated with High School. In the development of the study, different strategies were used, such as thematic workshops, research into its network of social relationships, conversation circles, group dynamics and the creation of an Interdisciplinary Cultural Mural. To analyze the information collected, a qualitative approach was chosen to understand the cultural values, representations, attitudes, opinions and habits of the students and their network of social relationships. We identified the local knowledge about plants; We described the use and conservation of medicinal plants; and we developed a roadmap for interdisciplinary collaborative activities. Local knowledge about medicinal plants proved to be an excellent topic to contextualize the teaching of environmental sciences, motivating dialogue between student-student, student-researcher and student-family and creating knowledge that went beyond the walls of the school.
Keywords: Plantas medicinais - Amazônia; Biodiversidade - Conservação; Medicina popular; CIENCIAS BIOLOGICAS; Saber local; Conservação da biodiversidade; Ensino contextualizado; Interdisciplinaridade